A CPFEM based theoretical analysis of strains resolved by the microstructural feature tracking method. Issue 1 (1st July 2022) - Li, R; Quey, R; Zhang, Y; Kobayashi, M; Oddershede, J; Juul Jensen, D
Abstract: In this work, it is investigated how grain boundaries influence the local strain determination by the microstructural feature tracking (MFT) algorithm. In this method, tetrahedra are used as the strain calculation unit. We apply the MFT processing procedure on data obtained by a crystal plasticity finite element modeling (CPFEM) simulation to explore the uncertainties in the calculated strains caused by grain boundaries. Effects of tetrahedron types and radius ratios are discussed.